2021
DOI: 10.1007/s44154-021-00008-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond dueling: roles of the type VI secretion system in microbiome modulation, pathogenesis and stress resistance

Abstract: Bacteria inhabit diverse and dynamic environments, where nutrients may be limited and toxic chemicals can be prevalent. To adapt to these stressful conditions, bacteria have evolved specialized protein secretion systems, such as the type VI secretion system (T6SS) to facilitate their survival. As a molecular syringe, the T6SS expels various effectors into neighboring bacterial cells, eukaryotic cells, or the extracellular environment. These effectors improve the competitive fitness and environmental adaption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…The role of T6SS in bacterial antagonism has been extensively explored in various environments [ 25 , 53 , 54 , 55 ]. However, recent data suggest that this system also plays an important role in combating oxidative stress [ 18 , 20 , 21 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of T6SS in bacterial antagonism has been extensively explored in various environments [ 25 , 53 , 54 , 55 ]. However, recent data suggest that this system also plays an important role in combating oxidative stress [ 18 , 20 , 21 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The T6SS system was first discovered and studied in the plant-associated bacterium Rhizobium leguminosarum that affects pea nodulation and nitrogen fixation (Bladergroen et al 2003 ). However, with the deepening of research, the T6SS has been demonstrated to have diverse functions (Lin et al 2021 ), including anti-bacterial (Trunk et al 2018 ) and anti-host activities (Coulthurst. 2019 ), mediating the uptake of metal ions (Lin et al 2017 ; Han et al 2019 ), resistance to environmental stress (Si et al 2017a ; Wan et al 2017 ), inhibition of bacterial infection in the host (Bendor et al 2015 ), and regulating the formation of bacterial biofilms (Lin et al 2015 ; Chen et al 2020 ).…”
Section: T6ssmentioning
confidence: 99%
“…is important for its biocontrol activity. The T6SS is a syringe-like structure resembling a phage tail capable of secreting effector proteins into targeted prokaryotic and eukaryotic cells [ 144 , 145 ]. This system has been recognized as a powerful antifungal weapon, and fungal-specific effector proteins, Tfe1 and Tfe2, have been identified.…”
Section: Biocontrol Mechanisms Of Pseudomonasmentioning
confidence: 99%